PROGRAM KEMITRAAN MASYARAKAT (PKM) PEMANFAATAN MEDIA POWTOON UNTUK DETEKSI DINI KEHAMILAN RISIKO TINGGI PADA IBU HAMIL - Suparni, Suparni; Aisyah, Risqi Dewi; Rachmani, Ferlinda Ainur (Poltekkes Kemenkes Riau, 2023)
Health promotion is an effort that aims to provide health messages to community groups so that people can implement healthy living behaviors. With health promotion, it is hoped that the public can have information related to health and efforts to prevent health problems itself because the provision of health promotion can be done by providing counseling about health to the community so as to increase public knowledge and attitudes in efforts to prevent health problems. In this digital era, the counseling media as a appliance to assist instructors giving education are variated, which one uses the Powtoon as an counseling media. The goal of PKM utilization of powtoon media for early detection of high risk pregnancy in pregnant women is to increase the knowledge of pregnant women about high risk pregnancy, how to handling the high risk during pregnancy, and determine high risk score with KSPR (Poedji Rochjati Scoring Card) score. The method used in this PKM activity is the teaching and learning process with Powtoon media. The results of this PKM for the knowledge of pregnant women guardians is an increase in the average pre-test score of 47,3 and the average post-test score is 89,6. The conclusion from this PKM is that this activity is able to increase the knowledge of pregnant women and stimulate the participation and involvement of pregnant women to participate in pregnancy class by health service facilities. Keywords: Powtoon Media, Early Detection Of High Risk Pregnancy, Health Promotion